Allergen immunotherapy using recombinant Culicoides allergens improves clinical signs of equine insect bite hypersensitivity - Graner, Anneli; Mueller, Ralf S.; Geisler, Johanna; Bogenstätter, Delia; White, Samuel J.; Jonsdottir, Sigridur; Marti, Eliane (Frontiers in Allergy, 2024)
IntroductionInsect bite hypersensitivity (IBH) is an IgE-mediated allergic dermatitis of horses caused by bites of Culicoides spp., sharing some common features with human atopic dermatitis. Allergen immunotherapy (AIT) using Culicoides whole-body extracts has limited efficacy. This study aimed to evaluate AIT with a pool of major Culicoides recombinant allergens in a prospective, double-blinded, placebo-controlled study.MethodsThe IBH lesion score was assessed during a pre-treatment year and first treatment year (May–October) in 17 horses and in May and July of a second treatment year. Nine horses were immunized subcutaneously 3× with a combination of nine r-allergens (20 μg each/injection) in alum and monophosphoryl lipid A (MPLA). Eight horses received a placebo. The immunization was repeated twice the following year. The specific antibody response to one of the AIT Culicoides r-allergens was assessed.ResultsIn the first treatment year, the decrease in average IBH lesion score was significantly larger in the AIT compared to the placebo group, with 67% of the AIT group and 25% of the placebo horses reaching >50% improvement of the average IBH lesion score. The response to the AIT was enhanced in the 2nd treatment year when 89% of the AIT vs. 14% of the placebo horses showed an improvement (p ≤ 0.01). IgG antibodies of all subclasses were induced, with IgG4/7 showing the most significant differences between groups. The post-AIT sera showed IgE blocking activity.DiscussionAIT using only a few injections of small amounts of r-allergens in alum and MPLA as immunomodulators seems a promising approach for the treatment of insect bite allergy.